2005
DOI: 10.1111/j.1365-3180.2005.00452.x
|View full text |Cite
|
Sign up to set email alerts
|

Can an integrated management approach provide a basis for long‐term prevention of weed dominance in Australian pasture systems?

Abstract: Broad-leaved weeds in pasture, such as Carduus nutans, Onopordum spp. and Echium plantagineum are a major problem for graziers in southern Australia. Previous attempts to combat these weeds with a single technique have only resulted in short-term success. An approach to long-term control, combining biological control with different grazing and herbicide strategies, was evaluated in an integrated weed management (IWM) programme, in south-eastern Australia. This IWM study was one of the few that has focused on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
4
16
0
Order By: Relevance
“…We found that the interactions between floral herbivory and two parameters that can be influenced by local weed management practices (survival to flowering and successful seed germination) predict population stasis across a wide range of parameter values, and probably explain the limited population growth and invasiveness of C. vulgare in Nebraska. This finding is consistent with the suggestion that multiple, interacting factors are generally needed for effective weed control (Shea, Thrall & Burdon 2000;Grigulis et al 2001;Huwer et al 2005).…”
Section: O N C L U S I O Nsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that the interactions between floral herbivory and two parameters that can be influenced by local weed management practices (survival to flowering and successful seed germination) predict population stasis across a wide range of parameter values, and probably explain the limited population growth and invasiveness of C. vulgare in Nebraska. This finding is consistent with the suggestion that multiple, interacting factors are generally needed for effective weed control (Shea, Thrall & Burdon 2000;Grigulis et al 2001;Huwer et al 2005).…”
Section: O N C L U S I O Nsupporting
confidence: 91%
“…This finding is consistent with the suggestion that multiple, interacting factors are generally needed for effective weed control (Shea, Thrall & Burdon 2000; Grigulis et al . 2001; Huwer et al . 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Fertilisers have been used to increase the palatability of Eragrostis curvula, and in combination with grazing management provided good control (Firn et al 2010). A treatment combination of herbicides and grazing has been effective for the control of Echium plantaginuem (Huwer et al 2005) and Carduus nutans (Shea et al 2006). Herbicides alter the morphology of E. plantaginuem making the rosettes more erect and available to grazing stock (Piggin 1979).…”
Section: Control Strategiesmentioning
confidence: 99%
“…Integrated management that not only focuses on biocontrol agents but also integrates multiple factors will be more likely to control this invasive weed effectively in the invaded range (Shea, Thrall & Burdon 2000; Grigulis et al . 2001; Huwer et al . 2005; Shea, Sheppard & Woodburn 2006).…”
Section: Discussionmentioning
confidence: 99%